Barrages romains du Portugal - António C. Quintela; José Manuel de Mascarenhas (Mélanges de la Casa de Velázquez)
Since the 1980s more than forty Roman dams have been identified in Portuguese territory. This article seeks to present them in their geographical and topographical context and to explain why they were built. It distinguishes two broad types – earthwork dams and masonry or concrete dams (i.e. plain stone walls or multiple walls with infilling). In most cases small or medium dams were intended to provide water supplies for Roman villae or for industrial or mining facilities. The authors present a closer analysis of the villae of Comenda (Setúbal), Pisões (Beja) and above all Cerro da Vila (Loulé), which are particularly interesting as regards water adduction and distribution from the dams. All the dams are listed and briefly characterised in table form.